2013
DOI: 10.1016/j.molcel.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing Regulates Biogenesis of miRNAs Located across Exon-Intron Junctions

Abstract: The initial step in microRNA (miRNA) biogenesis requires processing of the precursor miRNA (pre-miRNA) from a longer primary transcript. Many pre-miRNAs originate from introns, and both a mature miRNA and a spliced RNA can be generated from the same transcription unit. We have identified a mechanism in which RNA splicing negatively regulates the processing of pre-miRNAs that overlap exon-intron junctions. Computational analysis identified dozens of such pre-miRNAs, and experimental validation demonstrated comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 73 publications
(73 reference statements)
3
95
0
Order By: Relevance
“…These results indicate that expression of these apparently linked miRNAs may be uncoupled in some settings. Finally, our data confirm previous analyses that identified miRNAs that span splice sites (Melamed et al 2013), supporting a role for alternative splicing in regulating the expression of specific miRNAs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results indicate that expression of these apparently linked miRNAs may be uncoupled in some settings. Finally, our data confirm previous analyses that identified miRNAs that span splice sites (Melamed et al 2013), supporting a role for alternative splicing in regulating the expression of specific miRNAs.…”
Section: Discussionsupporting
confidence: 89%
“…A previous analysis of existing expressed sequence tags (ESTs) and mRNAs revealed a class of pre-miRNA sequences that span intronexon junctions such that splicing prevents processing of these miRNA hairpins by the microprocessor complex (Melamed et al 2013). We were able to confirm the existence of pri-miRNAs with this configuration using our assemblies (Supplemental Table S4).…”
Section: Alternative Splicingsupporting
confidence: 57%
“…Our data indicate that the expression of oncogenic miRNAs is superimposed over that of the tumor-suppressive miRNAs as a net gain by HR HPV infection. It is possible that the posttranscriptional regulation could also play a role in this net gain, because p53 interacts with Drosha/p68 complex to facilitate Drosha-mediated primarymiRNA processing of certain miRNAs (27) and some miRNAs derived from intron regions are coupled to RNA splicing (59,60).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus possible that ESRP2 suppresses ␦EF1 and SIP1 by regulating miRNA expression. Melamed et al (37) recently reported that the alternative splicing machinery competes with the miRNA processing machinery when a pre-miRNA sequence overlaps with active splice sites. However, EMT-associated pre-miRNA sequences (miR-34, miR-200 family, and miR-9) do not overlap exon-intron junctions, ruling out such a mechanism.…”
Section: Discussionmentioning
confidence: 99%